A Hierarchical Taxonomy of Psychopathology Can Transform Mental Health Research. (May 2019) - Conway, Christopher C.; Forbes, Miriam K.; Forbush, Kelsie T.; Fried, Eiko I.; Hallquist, Michael N.; Kotov, Roman; Mullins-Sweatt, Stephanie N.; Shackman, Alexander J.; Skodol, Andrew E.; South, Susan C.; Sunderland, Matthew; Waszczuk, Monika A.; et al.
For more than a century, research on psychopathology has focused on categorical diagnoses. Although this work has produced major discoveries, growing evidence points to the superiority of a dimensional approach to the science of mental illness. Here we outline one such dimensional system—the Hierarchical Taxonomy of Psychopathology (HiTOP)—that is based on empirical patterns of co-occurrence among psychological symptoms. We highlight key ways in which this framework can advance mental-health research, and we provide some heuristics for using HiTOP to test theories of psychopathology. We then review emerging evidence that supports the value of a hierarchical, dimensional model of mental illness across diverse research areas in psychological science. These new data suggest that the HiTOP system has the potential to accelerate and improve research on mental-health problems as well as efforts to more effectively assess, prevent, and treat mental illness.